2002
DOI: 10.1034/j.1399-6576.2002.460106.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anaesthesia and surgery on the circadian rhythm of melatonin

Abstract: Our findings suggest that anaesthesia in conjunction with surgery acutely disturbed the normal circadian rhythm of melatonin by delaying the onset of nocturnal melatonin secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 32 publications
7
96
2
6
Order By: Relevance
“…Any alteration detected in the timing of circulating melatonin is therefore considered to reflect altered functioning of the suprachiamatic clock. However, in all these studies the role of surgery itself has not been excluded (for discussion, see eg Karkela et al, 2002). Using propofol, the present data supports our working hypothesis that general anesthesia per se alters daily temporal organization.…”
Section: Clinical Significancesupporting
confidence: 80%
See 3 more Smart Citations
“…Any alteration detected in the timing of circulating melatonin is therefore considered to reflect altered functioning of the suprachiamatic clock. However, in all these studies the role of surgery itself has not been excluded (for discussion, see eg Karkela et al, 2002). Using propofol, the present data supports our working hypothesis that general anesthesia per se alters daily temporal organization.…”
Section: Clinical Significancesupporting
confidence: 80%
“…Data from human studies have shown disturbances in the pattern of melatonin secretion following general anesthesia associated with surgery Karkela et al, 2002;Reber et al, 1998). Secretion of melatonin by the pineal gland is commonly used as a circadian phase marker (Cassone et al, 1993;Pevet, 2003).…”
Section: Clinical Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Human studies show alterations in melatonin levels after general anaesthesia and surgery (20)(21)(22). All of these studies discuss the effects of anaesthesia or pain related to surgery as the reason for sleep disorders or delirium.…”
Section: Discussionmentioning
confidence: 99%